A new species of parasitic copepod of the genus lernaeenicus lesueur, 1824 (siphonostomatoida: pennellidae) from the torpedo scad megalaspis cordyla (linnaeus) off Kerala coast of Arabian Sea, India - Panakkool Thamban Aneesh; Ameri Kottarathil Helna; Appukuttannair Biju Kumar; Balu Alagar Venmathi Maran (Taylor & Francis, 2021)
A new species of parasitic copepod of the genus Lernaeenicus Lesueur, 1824 (Siphonostomatoida: Pennellidae) parasitizing the torpedo scad Megalaspis cordyla (Linnaeus) collected from the Arabian Sea, off Kerala coast, India is described and illustrated. The new species, Lernaeenicus megalaspis sp. nov., can be distinguished from its other 32 congeners by the following features: (i) cephalosome 1.5 times longer than broad; (ii) presence of three stout posterior horns on the cephalosome, one median and two lateral, all sub-similar and apically round and blunt; (iii) neck 4.6 times as long as trunk; (iv) abdomen slightly longer than trunk; (v) 4-segmented antennule, and (vi) maxilla, third segment narrow, longer than second, segment 1 slightly broader than others and lateral border with two small spine.